2002
DOI: 10.1002/pc.10422
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chemical surface modification on the performance of sisal‐polyester biocomposites

Abstract: This article concerns the effectiveness of various types and degrees of surface modification of sisal fibers involving dewaxing, alkali treatment, bleaching cyanoethylation and viny1 grafting in enhancing the mechanical properties, such as tensile, flexural and impact strength, of sisal‐polyester biocomposites. The mechanical properties are optimum at a fiber loading of 30 wt%. Among all modifications, cyanoethylation and alkali treatment result in improved properties of the biocomposites. Cyanoethylated sisal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 16 publications
4
78
0
Order By: Relevance
“…Consequently, mercerization or more general alkali treatment had a lasting effect on the mechanical behavior of flax fibers, especially on fiber strength and stiffness (Gassan and Bledzki 1999). Several other studies were conducted on alkali treatment (Mishra et al 2002;Joseph et al 2000;Sreekala et al 2000). They reported that mercerization led to the increase in the amount of amorphous cellulose at the expense of crystalline cellulose and the removal of hydrogen bonding in the network structure.…”
Section: Surface Chemical Modifications Of Natural Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, mercerization or more general alkali treatment had a lasting effect on the mechanical behavior of flax fibers, especially on fiber strength and stiffness (Gassan and Bledzki 1999). Several other studies were conducted on alkali treatment (Mishra et al 2002;Joseph et al 2000;Sreekala et al 2000). They reported that mercerization led to the increase in the amount of amorphous cellulose at the expense of crystalline cellulose and the removal of hydrogen bonding in the network structure.…”
Section: Surface Chemical Modifications Of Natural Fibersmentioning
confidence: 99%
“…The elongation at break of the composites with chemically modified fiber was attributed to the changes in the chemical structure and bondability of the fiber. Alkali treated (5%) sisal-polyester biocomposite showed about 22% increase in tensile strength (Mishra et al 2002). Ichazo et al (2001) found that adding silanetreated wood flour to PP produced a sustained increase in the tensile modulus and tensile strength of the composite.…”
Section: Mechanical Properties Of Compositesmentioning
confidence: 99%
“…However, the drop in tensile strength at 8% NaOH could be explained by the excess removal of cellulose content at the surface of the fiber by the high concentration of alkali, which would damage the fiber's structure (Manalo et al 2015). Different types of natural fibers have different optimum concentration of alkali during the pretreatment process, which later affects the performance of the composites (Misra et al 2002;Lee and Wang 2006;Boopathi et al 2012). The different chemical compositions between fibers and matrix limit their bonding.…”
Section: Fiber Pretreatment and Coupling Agentmentioning
confidence: 99%
“…A high cellulose content and low microfibril angle are desirable properties in a fibre to be used in polymer composites 3 . The properties of fibre-reinforced composites depend on many factors such as fibre-matrix adhesion, volume fraction of fibre, fibre aspect ratio, fibre orientation as well as stress transfer efficiency of interphase 9,10 . The potential strength and toughness of natural fibres have not yet been fully exploited because of poor chemical compatibility between hydrophilic fibre and the more hydrophobic polymer matrix.…”
Section: * Author For Correspondencementioning
confidence: 99%